PENGARUH PEMANASAN OHMIC DAN KANDUNGAN ANTOSIANIN PUREE KULIT BUAH MANGGIS (Garcinia mangostana L) - Komang Ariyati; Salengke; Supratomo (Depertemen Teknologi Pertanian Universitas Hasanuddin, 2020)
Anthocyanin compound in mangosteen (Gracinia Mangostana L) rind can be used as a natural coloring to replace synthetic coloring and also a solution to reduce rind waste from mangosteen as well. Aim of this research is to know the characteristic of ohmic heating, degradation kinetics, and anthocyanin activation energy of mangosteen rind puree. Method the research is done by ohmic heating mangosteen (Gracinia Mangostana L) rind puree at 70°C, 90°C, and 110°C for period time 30, 60, and 90 minutes. The samples of these ohmic heating will be seen under spectrophotometer uv-vis to know amount of anthocyanin from different treatments. This research shows that at 70°C for 30 minutes, the anthocyanin is at its peak shown by number 4585.860 mg/l. Meanwhile at 110°C for 90 minutes, the anthocyanin is at its lowest shown by number 1787.568 mg/l. Result reveals that anthocyanin level is affected a lot by different temperature and time length of mangosteen rind heating. The higher and longest the heating, the lower level of anthocyanin consisted. Anthocyanin shows high temperature dependency by number 62.1812 kJ/mol as activation energy.